DESIGN OF OFFICE AT SUDIRMAN CENTRAL BUSINESS DISTRICT (SCBD) - Christine, Millenia
The building design is done for an office building consisting of 13 floors and 2 basements. The building is designed as a dual system with special moment-resisting frame and special reinforced concrete shear wall with loads based on SNI 1727- 2020 and earthquake resistance planning is carried out based on SNI 1726-2019. Preliminary design calculations were performed manually while the modeling and structural analysis were performed using ETABS. The design of the building is carried out using a two-stage analysis. This building is planned using a semi topdown method. Geotechnical design is carried out based on SNI 8460-2017. Diaphragm wall is used as retaining wall with slab as reinforcement which is designed using PLAXIS 2D. For the foundation design, manual calculations were carried out using the rivet method and software calculations using LPILE, GROUP, and PLAXIS 3D. For construction engineering management, work breakdown structures, construction implementation methods, project schedules, and stages of construction cost plan are made. Keywords: semi top-down, bored pile foundation, diaphragm wall, LPILE, GROUP, PLAXIS 2D, PLAXIS 3D, dual system with special moment resisting frame, special reinforced concrete shear wall, earthquake resistant structure, twostage analysis, construction method, project schedule, construction cost plan.